Spatial analysis of Schistosoma Haematobium infection among school children in a rural sub-district of South Africa: an application of geographical information systems (2009) - Azongo, Kwaku Daniel (My University, 2009)
Background Assessing risk of schistosomiasis requires knowledge of the spatial distribution of the disease and its association with demographic, socioeconomic, behavioural, and environmental factors over time and space. The objective of this study was to advance such knowledge by analyzing the spatial distribution of schistosoma haematobium infections in relation to the demographic attributes and environmental covariates of the Africa centre Demographic Surveillance Areas (DSA) in rural KwaZulu-Natal. The study also examined the association between household socio-economic conditions and rates of S. haematobium infection with particular emphasis on the impact of pipe water on rates of infection. Methods The study is a crosses sectional study, involving all 33 primary schools in Africa Centre DSA. 2110 grade five and six children took part in the study. Statistical analysis was done using chi square tests to compare statistical significant differences between sex and age groups. Bivariate and multivariate logistic regression models were used to explore factors that are significantly associated with infection. Spatial analysis was done to examine the spatial distribution of the disease using geographical information systems techniques. Microscopic analysis of the urine samples was done using the filtration technique. Results Of the 2110 school children who were screened for infection, 347 tested positive for the presence of iv S. haematobium, representing an overall prevalence of 16.6%. Prevalence levels were higher in boys (20.8%) than females (8.5%) (P<0.001). 57.6% were heavily infected (eggs ≥50 eggs per 10ml urine) as compared to 42.5% who had light infection (eggs<50 eggs/10ml of urine). Whereas, prevalence was significantly age-dependent (Pearson chi2 (3) = 28.4184, P< 0.001), intensity of infection was not significantly age dependent (Pearson chi2 (3) = 3.2579, P<0.354). Altitudinal variation, access to portable water, toilet, and distance to water bodies were significantly associated with infection. Prevalence of infection was clustered around the Eastern part of the study area. Conclusion While there may be several factors associated with schistosoma infection in the study area's school children; age, sex, water contact behaviour, homestead altitude and distance to permanent water bodies, were the most significant risk factors explaining the spatial distribution of S. haematobium infection in the Africa Centre DSA. Selective Mass treatment of S. haematobium infection in 7 clustered areas is recommended for the control of the disease.
M.Sc. (Med.), Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: Schistosoma Haematobium; bilharzia; geographical information; epidemiology